Ingrid Bergman, "The Maria Cut, " and the Construction of a Hollywood Persona. (2nd November 2018) - Biddle-Perry, Geraldine
Abstract: Hair, or rather its cutting, styling, and dressing, operates as a powerful cultural form in cinematic practices and filmic discourses. This essay explores the richness of this resource and its exploitation in the construction of a Hollywood persona, specifically that of Ingrid Bergman, and her portrayal of the emotionally damaged Maria in Paramount Pictures' adaptation of Ernest Hemingway's novel, For Whom the Bell Tolls . The focus is on Maria's shaven head that is invested with huge symbolic significance in Hemingway's narrative and its onscreen transformation. Bergman's carefully crafted gamine curls were swiftly dubbed the "Maria cut." Albeit now largely forgotten, the style marked a new era in cinematic hairdressing and its role in the apparatus of star image making. The essay examines studio boss David O. Selznick and Bergman's search for an authentic screen persona that could broker the dual demands of a Hollywood glamour aesthetic and a sense of personal and professional agency. In the context of the film's release in the US and Britain in the Second World War, the Maria cut embodied a new kind of femininity that solicited and sustained fans' interests who flocked to the hairdressers to replicate the look.